ATTRIBUTE MEASUREMENT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AMONG EMPLOYEES (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Organizational citizenship behaviour in which employees are willing to go above and beyond their prescribed role requirements. Organizational behaviour provides knowledge to managerial employees on the understanding ofemployees behaviour for the purpose of improving cooperation within them in order to achieve the organization's objective. Successful organizations need employees who will do more than their usual job duties and provide performance that is beyond expectations. The study was conducted in Sakthi Sugars limited – Soyas division, Pollachi by measuring the demographic profile and Organizational citizenship behaviour over 117 employees were taken as sample size for the study. The SPSS software was used for the measurement of Organizational citizenship behaviour. The measurement of Organizational citizenship behaviour in company shows that the someof the OCB attributes seems to be lower among employees. The managers can train the employees to improve these two factors. When these two factors become stable among employees the growth of the organisation will also improve.